So You Want to Sing Musical Theatre: A Guide for Performers - Flynn, Amanda (Rowman & Littlefield Publishers, 2022)
From television shows like Glee and Smash to the phenomenon of the Broadway show Hamilton, musical theatre has never been more popular. In So You Want to Sing Musical Theatre, Updated and Expanded Edition, Broadway vocal coach Amanda Flynn provides an in-depth look at the skills needed to successfully sing and teach this repertoire. Fully updated to meet the current needs of the profession, this new edition covers a vast array of topics with even deeper discussion: musical theatre history; repertoire; genres used in productions; basic singing voice science; vocal health; audio equipment and microphones; vocal production of musical theatre sounds; acting, dancing, and other movement; working with kids; and auditioning at all levels. The book also includes profiles of Broadway singers that explores their training, methods of vocal upkeep, and advice for singers and teachers. The So You Want to Sing series is produced in partnership with the National Association of Teachers of Singing. Please visit www.nats.org to access style-specific exercises, audio and video files, and additional resources.